Experiencing Leonard Bernstein : a listener's companion - LaFave, Kenneth (Lanham : Rowman & Littlefield, 2015)
Leonard Bernstein is a household name. Most know him for his classic musical reworking of Shakespeare's Romeo and Juliet as Broadway's West Side Story. But Bernstein accomplished so much more as a composer, and his body of work is both broad and varied. He composed ballets (Fancy Free, Facsimile, Dybbuk), operas (Trouble in Tahiti, Candide, A Quiet Place), musicals (On the Town, Wonderful Town), film scores (On the Waterfront), symphonies, choral works, chamber music pieces, art songs, and piano works. In Experiencing Leonard Bernstein: A Listener's Companion, Kenneth LaFave guides readers past Bernstein's famously tortured personal problems and into the clarity and balance of his Serenade after Plato's Symposium for Violin and Orchestra, the intense drama of his music for On the Waterfront, the existential cosmography of his three symphonies, and his vibrant works for the musical stage. Perhaps the most famous American classical musician born in the twentieth century, Bernstein divided his time between composing, conducting, writing, and teaching, a busy schedule - especially his conducting of major orchestras - that set his work as composer at a disadvantage. Often generated in short spurts, his work carries an urgency - and even an element of improvisational genius - that he flavored with his eclectic embrace of jazz, folk song, Jewish cantorial music, and innovations in contemporary classical theory. The result is a body of work that is beguilingly melodic, incomparably rhythmic, and irrepressibly individual. Experiencing Leonard Bernstein: A Listener's Companion is the ideal work for any reader seeking to learn how to listen across the spectrum of Bernstein's musical output. - Back cover.
Father, son, and music -- Celebrity -- Age of anxiety -- Trouble in Tahiti and Wonderful town -- On the waterfront and Serenade after Plato's Symposium -- Candide -- West side story -- Kaddish and Chichester Psalms -- Mass and the Norton lectures -- Last works and legacy.
Includes bibliographical references (pages 187-188), discography (pages189-190) and index.
Keywords: Bernstein, Leonard, -- 1918-1990 -- Criticism and interpretation